Study of John Ruskin’s Treatises on Honesty in Architecture - A. Al-Sadkhan (Recent Research Advances in Arts and Social Studies Vol. 5, 2024)
The revelation of Ruskin’s treatises’ strengths through this analytical pause (the subject) helps contemporary architects adopt the principles that Ruskin advocated, especially in the field of ethics. Most critics of architecture agree that Ruskin has a positive impact on architecture just as he hurts it. His treatises are sometimes superficial, extremist, and individualistic, and they oppose one of them to the other, which leads some critics to attack him harshly and stand against him. Ruskin lived in a crowded with different intellectual and sometimes contradictory climates and saw many thoughts, politics, sociology, science, and industry changes. Ruskin was only the victim of ideological dualism, which caused some of his treatises’ contradiction and superficiality despite others’ depth. Ruskin’s theoretical aspect was not complete with the practical aspect because he never cared about applied arts. Ruskin represented what might be called a "man of letters," interested in many diverse topics, such as the diversity of human life itself. The aim is to reveal contradictions and superficiality, specifically those implied in the chapter of "Lamp of Truth," and return them to the duality of his ideology, the gap between theory and practice that he suffers from, or both. This chapter is not an attempt to seek excuses for Ruskin. Still, an effort to understand his treatises, thus enabling the man not to be enthusiastic to all his treatises without discrimination for the reference of any of them and vice versa be entirely opposed. The climate of the petty bourgeoisie justifies many of his reactionary ideas in his refusal to use new materials and his separation of architecture from construction. Thus, he is the son of his ideology, unlike his proposals that dealt with honesty from an internal view in isolation from reality and its ideologies. The internal view of Ruskin’s thoughts enables a profit gained from those who are immortal, which makes him considered among the great philosophers and thinkers of different ages and eras.